‘How a Kaynana Should Behave?’ Discussions on the Role of Mothers-in-Law in Two Gün Groups - Berna Ekal (European Journal of Turkish Studies)
Gün [day], as a specific form of rotating savings and credit associations in urban Turkey, is a distinct ground for women where middle-class values and norms are performed. In this context, the discussions on being a kaynana [mother-in-law] help us to consider the ways in which the notion of conjugal family is central to the self-perception of women. To oppose the role of kaynanas ‘in the past’ is women’s way of claiming to comply with what they perceive to be the ‘modern’ way of forming a family and, hence, of being ‘modern’. This, in turn, helps us to reconsider the ways in which kinship roles are elaborated in different contexts and shows that the ideas about the proper kinship roles shape the relation of people to the people other than their kin.